1998
DOI: 10.1016/s0370-2693(98)00654-6
|View full text |Cite
|
Sign up to set email alerts
|

Quark-meson coupling model with constituent quarks: Exchange and pionic effects

Abstract: The binding energy of nuclear matter including exchange and pionic effects is calculated in a quark-meson coupling model with massive constituent quarks. As in the case with elementary nucleons in QHD, exchange effects are repulsive. However, the coupling of the mesons directly to the quarks in the nucleons introduces a new effect on the exchange energies that provides an extra repulsive contribution to the binding energy. Pionic effects are not small. Implications of such effects on observables are discussed.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…Although this seems to be a more complex system than that considered in [21], in fact it is possible to rescale the variables so that the analysis is very nearly identical to that in [21]. To begin with, define 8) and rescale the coordinates toR = αR/γ,τ = ατ /γ,λ = αλ/γ. Then writing…”
Section: Constructing the Instantonmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this seems to be a more complex system than that considered in [21], in fact it is possible to rescale the variables so that the analysis is very nearly identical to that in [21]. To begin with, define 8) and rescale the coordinates toR = αR/γ,τ = ατ /γ,λ = αλ/γ. Then writing…”
Section: Constructing the Instantonmentioning
confidence: 99%
“…In general, this would not conflict with observation because the lifetime of the present vacuum would be far longer than the age of the universe. Indeed, the possibility that we live in a metastable state was mooted long before the discovery of the Higgs [8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…The effects of the nuclear medium on the intermediate D and D * mesons are calculated with the quark-mesoncoupling (QMC) model [9]. The QMC model is a relativistic field theory model, where effective scalar (σ ) and vector (ω and ρ) meson mean fields are coupled directly to the light u and d quarks confined in a bag (or by a potential [10]). A very reasonable description of saturation properties of nuclear matter and of single-particle energy levels of finite nuclei is achieved in this model -for a review see Ref.…”
Section: J/ψ Binding To Nuclear Mattermentioning
confidence: 99%
“…Medium effects on the intermediate D and D * mesons are calculated in the context of the quark-meson-coupling (QMC) model [20]. This is a relativistic mean field model of nuclear matter, in which effective meson degrees of freedom are coupled directly to quarks confined in a bag (or confined by a potential [21]). Using scalar-isoscalar σ , vector-isoscalar ω, and vector-isovector ρ mean fields that couple(with adjustable coupling constants) to the light u and d quarks is sufficient to achieve a reasonable description of saturation properties of nuclear matter as well as energy levels of finite nuclei -a review on the model and a large collection of results can be found in Ref.…”
Section: J/ψ Binding To Nuclear Mattermentioning
confidence: 99%